2014
DOI: 10.1016/j.abb.2014.07.022
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNAs and long non-coding RNAs in the pathology, diagnosis, and management of melanoma

Abstract: Melanoma is frequently lethal and its global incidence is steadily increasing. Despite the rapid development of different modes of targeted treatment, durable clinical responses remain elusive. A complete understanding of the molecular mechanisms that drive melanomagenesis is required, both genetic and epigenetic, in order to improve prevention, diagnosis, and treatment. There is increased appreciation of the role of microRNAs (miRNAs) in melanoma biology, including in proliferation, cell cycle, migration, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 180 publications
(177 reference statements)
0
97
0
1
Order By: Relevance
“…This cluster is essential for inhibiting the proapoptotic moderator, Bcl-2L11 (BIM). Similar to this cluster, Georgantas et al reported that miR-506-514 cluster on chromosome X is overexpressed in melanoma (1,23,24). Overall, several miRNAs have been reported as key regulators of cell production, including miR-786-3p, miR-214, miR-155, and miR-126 (1).…”
Section: Cell-cycle Regulatory Overexpressed Mirnasmentioning
confidence: 79%
See 4 more Smart Citations
“…This cluster is essential for inhibiting the proapoptotic moderator, Bcl-2L11 (BIM). Similar to this cluster, Georgantas et al reported that miR-506-514 cluster on chromosome X is overexpressed in melanoma (1,23,24). Overall, several miRNAs have been reported as key regulators of cell production, including miR-786-3p, miR-214, miR-155, and miR-126 (1).…”
Section: Cell-cycle Regulatory Overexpressed Mirnasmentioning
confidence: 79%
“…The small cell protein, WEE1 G2 checkpoint kinase (WEE1), as a mitotic inhibitor kinase, is another target of the cell cycle inhibitor, miR-195. As demonstrated by Watanabe et al in 2013, depletion of WEE1 due to miR-195 attachment enhances cell proliferation (1,14,15). Furthermore, in a study by Felicetti et al and Igoucheva et al, miR-221 and miR-222 were shown to be overexpressed.…”
Section: Cell-cycle Regulatory Overexpressed Mirnasmentioning
confidence: 86%
See 3 more Smart Citations